(untitled) (Eurasian Research Bulletin, 2023)
The development of artificial intelligence (AI) starts in the 1950-year whit lot of skepticism. With the development of informational technologies, skepticism related to the AI is decreasing ant its applicability is increasing. AI shown special usage in the management of the complex system as well as the help for humans in different kinds of processes. One of the most frequently used AI is in the business where is used for the decision-making process support, making different kind of the simulations as well as the base for the developing competitive advantage of the organization